Preparação, caracterização e avaliação do potencial adsorvente e oxidante de partículas magnéticas recobertas por carbono proveniente de polímeros - Lilian Amaral de Carvalho (2012)
In this work we report an easy way to prepare magnetic particles coated with carbon using hematite and polymers as starting materials. We also studied the potential of these materials as oxidants and adsorbents using methylene blue (dye), dibenzothiophene (sulfur containing molecule), quinoline (nitrogen containing molecule), chloramphenicol(drug), Pb2+ and Cd2+ (toxic metals). The polymers used as carbon source were polyethylene terephthalate (PET), expanded polystyrene (EPS) and carbopol (CARB). The materials prepared from PET and carbopol have higher carbon content and surface areas in comparison with the one obtained from EPS. The magnetic carbonaceousmaterials obtained from these polymers present a large adsorption of polar species and are able to perform oxidation reactions, even though part of the magnetic core was oxidized. The material obtained from EPS does not adsorb any of the contaminants studied, but was able to catalyze oxidation reactions without degradation of its magneticcore